TECHNOLOGY USE IN NURSERY AND PRIMARY EDUCATION IN DEVELOPING LANGUAGE SKILLS - Mamatkulov Jakhongir Ubaydullo o‘g‘li, (PEDAGOGS, 2025)
Annotation. This article studies which and how Information and Communications Technologies (ICTs) are used by nursery and primary education in-service teachers as reported by their pre-service teacher trainees after observations in their practicum in two provinces in Spain, Alcalá de Henares- Guadalajara and Navarre. Results indicate that in-service teachers tend to use traditional technological tools (audio f‍iles, video f‍iles, multimedia, games, Microsoft Word, interactive whiteboards) more than social networking (Facebook, blogs or wikis) both for teaching and for organisational purposes. Thus, more training in recent applications seems necessary to get ICT social applications into education.